Analisis Rasio Keungan Untuk Mengukur Kinerja Keuangan: Studi Pada Pt Semen Indonesia , Tbk Yang Terdaftar Di Bursa Efek Indonesia Tahun 2022-2023 - Reza Amanda Bahtiari; Puput Anggreani; Novita Damayanti; Revina Rahma Sari; Widia Puspita Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to determine and assess the level of health of the company PT Semen Indonesia TBK as one of the companies in Indonesia and to measure its overall performance, so that the company can shine and be useful improve its quality. This research uses quantitative methods. This assessment tool is an adaptation of the Liquidity Ratio, Solvency Ratio, Profitability Ratio methods.The object of this research is the company PT Semen Indonesia TBK. This research method uses a quantitative descriptive method. The results of the research found that there was a decline in 2023 in the Quick ratio which decreased on a scale below 1, namely 0.949, which means that the company is considered unable to fulfill or pay debts smoothly in the cycle operational, the solvency ratio is in a stable condition because the company can demonstrate its ability to pay its obligations, the profitability ratio is considered very small because the profit received is still far from the 5% scale and it can be said that the profit value is not healthy. It is hoped that PT. Semen Indonesia Tbk can pay attention to and analyze the financial ratios produced based on periodic financial reports, so that PT. Semen Indonesia Tbk can improve its finances significantly